Full of grace and truth: the sacramental economy according to Thomas Aquinas - Vnuk, Joseph (2013)
Neo-Thomism misread Aquinas by trying to find in him answers to questions posed by Descartes and Kant, producing a theology that people like Chauvet rightly abandoned. This thesis, on the other hand, proposes a decidedly pre-modern reading of Thomas. It begins with two basic structures of Thomas' thought - a threefold notion of truth (so that truth is ontological as well as epistemological), and an understanding of exitus-reditus that shows its links to “archaic” concepts such as the hau of the Maori. Then it considers human life in terms of merit and thus “economy,” (exchange of valuables); but this economy is a gift economy, and here we consider the gift in the light of Seneca (whom Thomas took as an authority) and Mauss, as well as using Allard's insights into how debt, particularly debt to God, generates what in Thomas takes the place of the Cartesian subject. In this light grace is seen as the spirit of the gift with which God graces us, giving rise to gratitude. We then consider Christ as graced and gracing us, first of all by our configuration to him in the sacraments (using the analogy of clothes), followed by a conformation in grace. We look at this in baptism and penance, but then we take the Eucharist as a three-fold sign, and show how it generates in us faith, hope and love. The unity of the sacrament as a gift is emphasised, and the cases of its division, such as fiction, the votum sacramenti, and circumcision are examined. As a Jew, Derrida gives insight into grace before the coming of Christ and the value of the sacrifice of Abraham, and in this way we can see how Thomas circumvents Derrida's critique of the gift. Finally we compare Thomas with Chauvet.